2021
DOI: 10.1038/s41592-020-01041-y
|View full text |Cite
|
Sign up to set email alerts
|

High-accuracy long-read amplicon sequences using unique molecular identifiers with Nanopore or PacBio sequencing

Abstract: High-throughput amplicon sequencing of large genomic regions remains challenging for short-read technologies. Here, we report a high-throughput amplicon sequencing approach combining unique molecular identifiers (UMIs) with Oxford Nanopore Technologies or Pacific Biosciences CCS sequencing, yielding high accuracy single-molecule consensus sequences of large genomic regions. Our approach generates amplicon and genomic sequences of >10,000 bp in length with a mean error-rate of 0.0049-0.0006% and chimera rate <0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
281
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(287 citation statements)
references
References 55 publications
6
281
0
Order By: Relevance
“…Accuracy is essential to many amplicon sequencing applications, and the level of accuracy achieved by Loop-Seq may open up new opportunities. Long-read amplicon sequencing using the PacBio and Oxford Nanopore technologies ( [12]; Eren 2019 [24];) has received increased recent attention, with encouraging results demonstrating that per-base accuracy exceeding common short-read approaches can be obtained by combining long-read sequencing with molecular methods such as the construction of PacBio circular consensus (CCS) reads and appropriate bioinformatics. In the bacterial profiling application, multiple studies have shown that substantial improvements in species and subspecies resolution can be achieved by sequencing the entire~1.5 kb 16S gene, rather than just segments of 100-500 bases as is most commonly practiced today, and that even greater resolution is achievable by extending the sequenced region to most or all of the rrn operon [30].…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy is essential to many amplicon sequencing applications, and the level of accuracy achieved by Loop-Seq may open up new opportunities. Long-read amplicon sequencing using the PacBio and Oxford Nanopore technologies ( [12]; Eren 2019 [24];) has received increased recent attention, with encouraging results demonstrating that per-base accuracy exceeding common short-read approaches can be obtained by combining long-read sequencing with molecular methods such as the construction of PacBio circular consensus (CCS) reads and appropriate bioinformatics. In the bacterial profiling application, multiple studies have shown that substantial improvements in species and subspecies resolution can be achieved by sequencing the entire~1.5 kb 16S gene, rather than just segments of 100-500 bases as is most commonly practiced today, and that even greater resolution is achievable by extending the sequenced region to most or all of the rrn operon [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings warrant larger studies in these and other dengue surveillance cohorts, as well as exploration of how this approach can be used for other arboviruses such as chikungunya and Zika viruses. Ideally, such studies should be coupled with advances in the accuracy of long-read deployable sequencing platforms that could permit near real-time intra-host variant construction ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…While its long-read length (of up to ∼1 Mb, [6]) makes it very attractive for the generation of de novo genome assemblies (see e.g. [6,7]), its low upfront costs (∼1000 USD) and its portability offer huge advantages for DNA-or metabarcoding experiments in countries with limited infrastructure and funds for molecular biomonitoring [8][9][10][11][12], and for teaching and local capacity building [13,14]. The use of the MinION has been extensively investigated for biodiversity research and biomonitoring projects (reviewed in [15]).…”
Section: Applications To Species Identificationmentioning
confidence: 99%